High-resolution, non-hydrostatic simulation of internal tides and solitary waves in the southern East China Sea. (February 2023) - Min, Wenjia; Li, Qun; Xu, Zhenhua; Wang, Yang; Li, Delei; Zhang, Peiwen; Robertson, Robin; Yin, Baoshu
Abstract: The slope area northeast of Taiwan Island in the southern East China Sea (ECS) is well known as a hotspot for both internal tides and internal solitary waves (ISWs) despite uncertainties regarding their specific source and generation mechanism. This study investigates the generation and evolution processes of internal tides and ISWs northeast of Taiwan Island in the southern ECS, based on a super-high-resolution and non-hydrostatic numerical simulation. ISWs create a complex spatial pattern in both satellite images and our simulation, with wave propagation in multiple directions, including onshore and offshore. These ISWs, with the largest amplitudes reaching ∼ 50 m, are mainly generated by two mechanisms: local tide-topography interactions and disintegration of internal tides remotely generated over I-Lan Ridge. Locally generated ISWs propagate in various directions owing to the complex topography, whereas ISWs generated by the disintegration of remote internal tides are more consistent in their pathways. Strong barotropic to baroclinic energy conversions occur over both Mien-Hua Canyon and North Mien-Hua Canyon. For the baroclinic tidal energy fluxes, the advection flux is comparable to the pressure-work term in shallow water, while the pressure-work flux dominates in deep water. The nonlinear energy flux terms in shallow water are more important for the supertidal than the tidal signals. The semidiurnal energy flux features a clockwise pattern over the double-canyon region, indicating the formation of partial standing waves. Highlights: ISW source and mechanism in the southern ECS are clarified by non-hydrostatic, super-high-resolution simulation. ISWs originate from local tide-topography interactions and disintegration of internal tides from I-Lan Ridge. Enhanced dissipation of internal tides occurs in Mien-Hua Canyon due to partial standing waves.